Magi. 17 : the labyrinth of magic. - Otaka, Shinobu; Werry, John (Translator) (VIZ Media, 2016)
"Aladdin continues his training in Magnoshutatt, but the situation there is difficult. Mogamett's goal is the creation of a country of magicians free of interference from normal humans. Aladdin and his friend Titus are against this, but there is little they can do. When war breaks out between Magnoshutatt and Leam, Aladdin and Titus are going to have to choose a side to fight on, and the choice won't be an easy one."--